FAMILY MANAGEMENT CHALLENGES (REMUNOM, 2023)
This article has the general objective of analyzing the challenges of family management in family businesses located in the municipality of Linhares-ES. To achieve this objective, the study used a bibliographic and field research methodology, with the participation of twelve administrators from three different companies belonging to this business model. The research addresses issues related to the challenges of family management, when a lack of professionalism and knowledge are present in business environments, seeking to understand how challenges arise and whether managers adopt measures to support this scenario in order to generate administrative stability in companies. . It is expected that the results obtained from this bibliographical and field research will contribute to a better understanding of the challenges that this management model faces, allowing efficient practices in different areas to promote operational performance and guarantee the productivity of these companies, which are important for economic and social development.